Analysis of carotenoid content of different oil palm fruitlets between ripe and unripe fruit bunches and its management / Anith Arina Mohd Shahrome and Alawi Sulaiman - Mohd Shahrome, Anith Arina; Sulaiman, Alawi (Faculty of Plantation and Agrotechnology, 2018)
Elaies Guineensis is the most planted commodity crop in Malaysia. In the year 2017. oil palm sectors contributed to around RM 71.5 billion towards the Malaysian economy. However, the current processing method of producing crude palm oil will deteriorate carotene content Carotenoids are natural chemical compounds that give palm oil its orange-red colour. These compounds are actually good for human health as it can strengthen body immunity system. So. The objective of this study was to determine the carotenoid content in ripe and unripe oil palm bunches, The analysis of oil samples was done using NIRS DAI 650. Apart from carotenoid content. Deterioration of Bleachability Index (DOBI) and Free Fatty Acid (FFA) content can also be obtained. Stalks were removed from bunches. A total of 1 kg fruitlets were boiled, mesocarps were peeled off and pressed in order to obtain the oil samples. Oil samples were taken to Kempas Laboratory to analyze its content. It is proven that ripe bunches contain the average carotene content of ±968.07 ppm compared to unripe bunches with only ±927.37 ppm. Extraction of this element should be done enormously in order to fulfil) the needs people in the countries that have serious health problems due to the insufficient amount of vitamin A in their bodies such as Africa and many more.